B7-H3-targeting Fc-optimized antibody for induction of NK cell reactivity against sarcoma - Hagelstein, Ilona; Engel, Monika; Hinterleitner, Clemens; Manz, Timo; Märklin, Melanie; Jung, Gundram; Salih, Helmut R.; Zekri, Latifa (Frontiers in Immunology, 2022)
Antibody-dependent cellular cytotoxicity (ADCC) of NK cells largely contributes to the success of monoclonal antibody (mAb) treatment in cancer. The B7 family member B7-H3 (CD276) recently receives intense interest as a promising target for immunotherapy, as it is overexpressed in many tumor entities, whereas expression on healthy tissues is rather limited. We here studied expression of B7-H3 in sarcoma, and found substantial levels to be expressed in various bone and soft-tissue sarcoma subtypes. To date, only few immunotherapeutic options for treatment of sarcomas that are limited to a minority of patients are available. We here used a B7-H3 mAb to generate chimeric mAbs with either wildtype Fc-part (8H8_WT) or a variant containing amino-acid exchanges (S239D/I332E) to enhance affinity to CD16 on NK cells (8H8_SDIE). In comparative studies we found that 8H8_SDIE triggers profound NK cell reactivity as shown by analysis of activation, degranulation, secretion of IFNγ and release of NK effector molecules, resulting in potent lysis of sarcoma cell lines and patient-derived sarcoma cells. Our results emphasize the potential of 8H8_SDIE novel compound for treatment of sarcomas, particularly since B7-H3 is expressed in bone and soft-tissue sarcoma independent of their subtype.